Fatigue as main symptom in an elderly multiple myeloma patient: a Case Report - Li, Xuanna; Li, Shuang; Chen, Junrong (Frontiers in Medicine, 2025)
IntroductionThe high prevalence of fatigue as an atypical clinical manifestation in general practice creates notable diagnostic challenges, particularly in geriatric patients.MethodsWe describe a case of an 80-year-old female presenting with fatigue, initially attributed to poorly controlled diabetes mellitus or upper respiratory infection, who was ultimately diagnosed with multiple myeloma after admitted to the Department of General Medicine at a general hospital. Initial diagnostic workup including physical examination revealed the presence of anterior thoracic mass with undetermined etiology. Laboratory analysis demonstrated characteristic hematological abnormalities: normocytic anemia (hemoglobin 91 g/L), significant hyperglobulinemia (serum globulin 76.18 g/L), and hypoalbuminemia (serum albumin 27.94 g/L), showing a reversed albumin-globulin (A/G) ratio of 0.37. Guided by Murtagh’s safe diagnostic strategy, comprehensive imaging studies including contrast-enhanced cervical, thoracoabdominal computed tomography (CT) and 18F-FDG PET-CT were performed. Histopathological confirmation was obtained from the gastric mass (CD138+/CD38+ plasma cell infiltration) and anterior mediastinal tumor (κ light chain restriction). Serum immunofixation electrophoresis revealed monoclonal IgA-κ paraprotein, while bone marrow aspiration demonstrated 80% clonal plasma cells. These findings collectively fulfilled the International Myeloma Working Group (IMWG) diagnostic criteria for multiple myeloma with extramedullary involvement.ResultsThe patient was transferred to Hematology Department for further therapy. Clinical reassessment at 6-week follow-up showed symptomatic improvement and anterior thoracic mass regression.DiscussionWe report a diagnostic case study of a MM patient whose initial presentation was fatigue, and clinicians should prioritize the overall condition, reduce diagnostic delays and improve therapeutic outcomes through early intervention strategies.